Relation Between Resistance Drift and Optical Gap in Phase Change Materials. Issue 10 (7th September 2020) - Martinez, Jose C.; Simpson, Robert E.
Abstract: The optical contrast in a phase change material is concomitant with its structural transition. These two are connected by first recognizing that Friedel oscillations couple electrons propagating in opposite directions and supply an additional Coulomb energy. As the crystal switches phase, this energy acquires time dependence and the Landau‐Zener mechanism operates, steering population transfer from the valence to the conduction band and vice versa. Spectroscopy suggests that the oscillator energy E 0 dominates the optical properties and a calculation involving the crystalline field and spin–orbit interaction yields good estimates for E 0 of both structural phases. Further analysis relates the optical gap with the crystalline‐field energy as well as activation energy for electrical conduction. This last property characterizes the amorphous phase, thereby furnishing a link between the crystalline field and the activation energy and ultimately with the resistance drift exponent. Providing optical means to quantify resistance drift in phase‐change materials (PCMs) could circumvent the need for fabricating expensive devices and performing time consuming measurements. Abstract : Optical contrast in phase change material accompanies structural transition. Friedel oscillations couple electrons supplying additional Coulomb energy. At phase change, this acquires time dependence; the Landau‐Zener mechanism steers population transfer from valence to conduction band and vice‐versa. The optical gap and activation energy are related. This last characterizes the amorphous phase, linking crystalline field, activation energy, and resistance drift.